Edukasi Virtual Efektif pada Penurunan Nyeri dan Peningkatan Activity Daily Living pada Kondisi Knee Osteoarhtritis - Yohanes Deo Fau; Angria Pradita (FORIKES, 2022)
Virtual education is an internet-based distance medicine that can be an effective and cost-effective alternative during the COVID-19 pandemic. The purpose of this study was to determine the benefits of virtual education on knee osteoarthritis after 6 interventions. This study is a quasi-experimental that compares a group of patients with knee osteoarthritis before and after being given virtual education described through a zoom meeting. The population of this study was 28 respondents at the Physio Move Care clinic during May-July 2021. The sample selection technique was purposive sampling, so that 20 patients were obtained. Virtual education is carried out by physiotherapists and respondents with 6 treatments for 2 weeks with physiotherapist supervision through zoom meetings. By using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) in the pre-virtual education phase, the median value = 3.00 and in the post-intervention phase = 1.50. Wilcoxon test results showed p value = 0.001. It was concluded that virtual education was effective in reducing pain and increasing daily living activities in patients with knee osteoarthritis.Keywords: virtual education; osteoarthritis; Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC)ABSTRAK Edukasi virtual merupakan pengobatan jarak jauh berbasis internet yang dapat menjadi alternatif yang efektif dan hemat biaya di masa pendemi COVID-19. Tujuan penelitian ini adalah untuk mengetahui manfaat edukasi virtua pada knee osteoarthritis setelah 6 kali intervensi. Penelitian ini merupakan kuasi eksperimen yang membandingkan satu kelompok penderita knee osteoarthritis sebelum dan sesudah diberikan edukasi virtual yang dijabarkan lewat zoom meeting. Populasi penelitian ini adalah 28 responden di klinik Physio Move Care selama bulan Mei-Juli 2021. Adapun teknik pemilihan sampel adalah purposive sampling, sehingga diperoleh 20 pasien. Edukasi virtual dilakukan oleh fisioterapis dan responden dengan 6 kali treatment selama 2 minggu dengan pengawasan fisioterapis melalui zoom meeting. Dengan menggunakan Western Ontario and McMaster Universities Osteoarhtritis Index (WOMAC) pada fase sebelum virtual edukasi diperoleh nilai median = 3,00 dan pada fase sesudah intervensi = 1,50. Hasil uji Wilcoxon menunjukkan nilai p = 0,001. Disimpulkan bahwa edukasi virtual efektif untuk menurunkan nyeri dan meningkatkan activity daily living pada pasien dengan knee Osteoarthritis.Kata kunci: edukasi virtual; osteoarthritis; Western Ontario and McMaster Universities Osteoarhtritis Index (WOMAC)